Kocia mama na indeksie, czyli o decyzjach komisji oceny i selekcji księgozbiorów bibliotek publicznych, szkolnych i pedagogicznych raz jeszcze = Cat Mum censured - on the decisions of committees for the evaluation and selection of public, school and pedagogical library collections, some further remarks - Korczyńska-Derkacz, Małgorzata (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article presents the situation in post-war Polish librarianship, especially in the period of growing ideological struggles. It focuses on the activities of committees for the evaluation and selection of library collections. The archival materials from the Archives of New Records in Warsaw (Archiwum Akt Nowych) and the State Archives in Wrocław (Archiwum Państwowe) were used to present the objectives of these commissions, their regulations, member profiles and the criteria for deciding the fate of books. The original protocols from the committees working in the 1950s were used to illustrate the method of reviewing the work of well-known authors such Maria Rodziewiczówna, Józef Meissner, Tadeusz Dołęga-Mostowicz,Wacław Sieroszewski, Włodzimierz Perzyński and Józef Weyssenhoff. The author also highlights the activities of the reviewing and evaluating in the field of socio--political and popular literature and propaganda brochures. Attention is drawn to the committees` work relating to the development of a model catalogue of books for a village library.
Keywords: archiwum; Archiwum Akt Nowych; Archiwum Państwowe we Wrocławiu; bibliotekarstwo; walka ideologiczna; komisja; księgozbiory; archives; State Archives in Wrocław; Archives of New Records; librarianship; ideological struggle; committee; book collections